Physical fitness and health indicators of basic, technical, and technological educational staff - Santos Maia, Ana Gabriela; Olinto, Markus Filardi Moura; Lins, Victor César Dias; Dutra, Maurílio Tiradentes (Journal of Health & Biological Sciences, 2025)
Objective: This study aimed to analyze health and physical fitness indicators of employees of a federal institution of education, science, and technology in Brasília. Methods: The sample consisted of 29 employees, including 16 men (38.1 ± 7.9 years; 80.7 ± 12.5 kg) and 13 women (40.1 ± 7.0 years; 64.0 ± 8.2 kg). The indicators analyzed were body mass index (BMI), systolic and diastolic blood pressure (SBP and DBP), handgrip strength (HGS), flexibility, VO2 max, and body composition. Data were analyzed using descriptive and correlational statistics. The indicators were compared to reference values considering sex and average age, and a comparison between men and women was also performed. Results: The results for men and women, respectively, were: BMI: 26.8 ± 3.8 and 24.2 ± 2.3 (P = 0.04); HGS: 45.8 ± 9.3 and 31.2 ± 6.0 (P < 0.001); flexibility: 22.6 ± 9.7 and 30.7 ± 5.4 (P = 0.01); VO2 max: 33.1 ± 4.9 and 30.4 ± 3.8 (P = 0.12); body fat percentage: 25.6 ± 6.5 and 36.4 ± 5.8 (P < 0.001); and muscle mass percentage: 35.3 ± 3.4 and 26.3 ± 2.9 (P < 0.001). Positive correlations were found between VO2 max and muscle mass percentage (r = 0.49; P = 0.007) and negative correlations between VO2 max and body fat percentage (r = -0.49; P = 0.008). Conclusion: The sample’s body fat percentage and VO2 max were classified as poor, and the BMI of the men indicated overweight. These findings highlight the need for guidance and interventions to improve health and physical fitness parameters in this population.